GENEALOGY OF CONCEPTS OF SUSTAINABLE DEVELOPMENT AND INCLUSIVE ECONOMIC GROWTH - Vladyslav Makhonin (Izdevnieciba "Baltija Publishing", 2020)
Given the ongoing reorientation of world economic dynamics from a model of sustainable economic development to a more perfect dialectically inclusive growth model, global scientific applied and theoretical thought requires a deeper understanding of the nature of these models of economic dynamics. Furthermore, a broader understanding of the nature and settings of the model of inclusive economic growth, declared by super-influential world institutions as the key social and economic modus of our time, should contribute to the improve-ment of its methodological aspect, which determines the success of the implementa-tion of the principles of inclusive economic growth in the policies of modern - both developed and developing - countries, as well as, thus, the level of well-being of the population. Applying the systemic and evolutionary approach, the author analyzed the interdisciplinary nature of the concepts of sustainable development and inclusive economic growth, as a result of which the multisystem historical origins of these concepts have been revealed and, thus, the understanding of the latter have been expanded. In particular, using the systemic and evolutionary approach, as well as relying on the works of the scientists mentioned below, specific examples in the development of science have been identified, which demonstrate the formation of a multisystem scientific paradigm in a period that spanned the gap on the historical canvas from the end of the 19th century to the middle of the 20th century. Accord-ing to the author, as well as a number of scientists, this paradigm has set the trend towards a multidisciplinary research. Based on the specific facts given in the article, in the author's opinion, it was under the influence of the above tendency that a model of sustainable economic development emerged in the 1970s, and a dialectically more perfect model of inclusive economic growth appeared at the turn of the 20th and 21st centuries.